Research on Design and Motion Control of Pure Rolling Wheel Mobile Robots - Peng Wang; Jianjun Nie; Xiaolin Xie; Hongzhen Yan (Jixie chuandong)
Aiming at the side slip problem of the wheeled mobile robot in the steering process， a pure rolling steering system is designed to avoid tire wear caused by wheel side slip. Based on this pure rolling steering system， a dual-power differential drive axle is developed， three special motion modes including ackerman steering， crab motion and in-situ steering are established， and the kinematic characteristics of the three modes are analyzed. The adopted H-type balance suspension structure can be adjusted adaptively according to the undulations of the road surface， which improves the mobile robot's ability to overcome obstacles. The feasibility of the structure is tested by setting up an experimental platform. Finally， based on the established steering motion control strategy and the kinematics model， and using the inversion method， the trajectory tracking control law is derived， and the effectiveness of the control law is verified by Simuink simulation.